Unexpected effect of hydroxyl radical on tellurium corrosion of the Ni–Mo–Cr–Nb based alloy. (15th August 2020) - Jiang, Li; Wang, Wei; Ye, Xiang-Xi; Li, Chao-Wen; Liang, Jian-Ping; Wang, De-Jun; Li, Zhi-Jun
Graphical abstract: Abstract: The unexpected effect of hydroxyl radical on tellurium corrosion of the Ni–Mo–Cr–Nb based alloy was first observed in this study. In the corrosion experiments with the quartz tubes as vessels, hydroxyl radicals are released from the quartz at the high temperature (700 °C) and then react with Cr atoms to form Cr2 O3 layers at the surface of the alloy, which significantly suppress the simultaneous corrosion process by tellurium vapor. This work reveals the origin of the well-known uncertainty and helps to develop the more reliable experiments in future.